The Effect of Electric Train Tracking Using the C-Access Application Using the Routing Method on Customer Satisfaction at PT KCI 2024 - Kurniawan, Johanes; Hutauruk, Paul S; Sihombing, Sarinah; Hapsari, Natalia Ayu; Nugroho, Sinung Tri; Syahanawa, Guti (Dinasti Research, 2025)
This study aims to analyze the effect of using the C-Access application on electric train tracking and customer satisfaction at PT KCI in 2024. This study evaluates the effect of tracking, application usage, and routing methods on customer satisfaction. The research objects include online library literature, Google Scholar, Mendeley, and other online academic media. The research methodology involves a systematic literature review (SLR) using open access e-books and e-journals. Data are processed using the latest version of SEM Smart PLS software. The results of the study indicate that: 1) train tracking has a significant effect on customer satisfaction; 2) the use of the C-Access application has a positive effect on customer satisfaction; and 3) the optimized routing method also has a significant impact on customer satisfaction.. The value of 0.761 or 76.1% states that the Tracking, Application and Routing Variables contribute 76.1% to the formation of the Customer Satisfaction Variable tendency, there is still 23.9% influence from other factors that are not discussed and included in this study. These findings are very important for improving service quality and customer satisfaction in the transportation management sector.